PENGARUH KEMANDIRIAN BELAJAR SISWA SMP TERHADAP KEMAMPUAN PENALARAN MATEMATIS - Lailatul Fajriyah; Yoga Nugraha; Padillah Akbar; Martin Bernard (Departement of Mathematics Education, 2019)
Research on the learning ability to understand student learning independence towards mathematical punishment abilities. The research method uses correlational methods with quantitative research. The population in this study were students of one of the junior high schools in the city of Bandung and the sample of this study were students of class IX F as many as 32 students. The material used is the material of Two Variable Linear Equation System (SPLDV) which has been taught in class VIII. The instrument in this study consisted of a mathematical punishment ability test of 5 items, then a non-test instrument in the form of an independent learning scale as many as 28 positive and negative revelations. The step that needs to be done in this study is the filling of the learning independence questionnaire, a mathematical punishment ability test. The results of this study concluded that positive learning independence on the ability of students to sentence 46.6% and 53.4% ​​by other factors related to student learning independence.